2020
DOI: 10.1186/s40662-020-00218-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ablation ratio on 5-year postoperative posterior corneal stability after refractive surgery: SMILE and FS-LASIK

Abstract: Background To investigate the impact of the ablation ratio on 5-year postoperative posterior corneal stability in myopic eyes after small incision lenticule extraction (SMILE) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK) surgery. Methods A prospective, nonrandomized, cohort study: 80 eyes of 43 patients underwent SMILE surgery and 63 eyes of 32 patients underwent FS-LASIK surgery at the EYE & ENT Hospital, Fud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…Despite larger optical zones improving visual acuity and reducing HOAs, larger optical zones require more tissue removal to achieve the same refractive power, leading to a smaller residual stromal bed [26] and limited potential for future enhancements. For every attempted diopter of myopic correction, an additional 3−4 microns of tissue is ablated with the 6.5 mm optic zone compared to the 6.0 mm optic zone, which may potentially increase the risk of ectasia [27] and forward displacement of the posterior cornea [28]. On the other hand, our data reflected a significant difference in rates of enhancement one year after LASIK, with the 6.0 mm group having higher rates of enhancement.…”
Section: Discussionmentioning
confidence: 66%
“…Despite larger optical zones improving visual acuity and reducing HOAs, larger optical zones require more tissue removal to achieve the same refractive power, leading to a smaller residual stromal bed [26] and limited potential for future enhancements. For every attempted diopter of myopic correction, an additional 3−4 microns of tissue is ablated with the 6.5 mm optic zone compared to the 6.0 mm optic zone, which may potentially increase the risk of ectasia [27] and forward displacement of the posterior cornea [28]. On the other hand, our data reflected a significant difference in rates of enhancement one year after LASIK, with the 6.0 mm group having higher rates of enhancement.…”
Section: Discussionmentioning
confidence: 66%
“…Changes in PCE after SMILE have been reported that PCE tended to decrease as compared with that preoperatively, and this decline remained stable from 1 week to a 5 years follow-up period ( 27 , 28 ). In the present study, changes in PCE in the higher myopia eyes were consistent with the previous studies in the higher and lower myopia eyes.…”
Section: Discussionmentioning
confidence: 89%
“…A PTA value of ≥40% was significantly associated with the development of corneal ectasia (Santhiago et al 2014). A modified PTA formula was proposed for SMILE (Moshirfar et al 2017), but due to its low practicability, the PAD, also named as MCCT index or ablation ratio, has been used in most studies for the evaluation of SMILE outcomes (Wu et al 2014;Li et al 2020;Liu et al 2021). The PSBT was demonstrated to affect corneal stability after laser ablation, and a minimum value of 60% was usually accepted by surgeons for LASIK (Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pairwise comparisons of the area under the ROC curve (AUC) were performed using DeLong's test. With a target power of 80% and significance level of 5%, we determined a 0.33-lm difference in PCE for a sample size of 161 eyes (Li et al 2020). Percentage ablation depth (PAD) was defined as the ratio of maximum lenticule thickness (MLT) to preoperative central corneal thickness (CCT).…”
Section: Statistical Analysesmentioning
confidence: 99%